Distinctive cognitive phenotypes in Parkinson’s disease patients with GBA mutations and without dementia: a multicentre cross-sectional retrospective study - Chiara Longo; Marco Liccari; Ruggero Bacchin; Costanza Papagno; Donatella Ottaviani; Raffaella Di Giacopo; Mauro Catalan; Alina Menichelli; Massimo Marano; Alessio Di Fonzo; Giovanni Duro; Carmela Zizzo; et al. (Clinical Parkinsonism & Related Disorders, 2025)
Background: Cognitive impairment is a major non-motor complication of Parkinson’s disease (PD). GBA mutations are associated with an increased risk, with PD-GBA+ patients typically showing earlier disease onset and faster cognitive decline. However, the specific cognitive phenotype of these patients remains unclear. Aim: To provide a detailed neuropsychological profile of PD-GBA+ patients compared to PD-GBA− patients. Methods: Data from 18 PD-GBA+ and 68 PD-GBA− patients were retrospectively analyzed. All participants underwent comprehensive neurological evaluations of motor and non-motor symptoms, along with a Level II neuropsychological assessment based on the MDS criteria for mild cognitive impairment (MCI). Patients with dementia were excluded. Results: PD-GBA+ patients showed significantly lower cognitive performance, particularly on the RAVLT immediate recall (RAVLT-IR, p < 0.001) and delayed recall (RAVLT-DR, p = 0.002). All PD-GBA+ patients exhibited an amnestic multi-domain MCI phenotype. In contrast, the PD-GBA− group predominantly showed a non-amnestic single-domain MCI, characterized by a dysexecutive profile. Additionally, PD-GBA+ patients had a higher prevalence of freezing of gait (p < 0.001), right-sided motor symptom lateralization (p = 0.011), and REM sleep behavior disorder (p = 0.006). Conclusions: PD-GBA+ patients exhibit a distinctive cognitive phenotype, already evident in the early stages of the disease. These results highlight the added value of Level II neuropsychological assessment in accurately characterizing the clinical phenotype and identifying patients at higher risk of developing dementia. Early cognitive profiling may thus contribute to more targeted monitoring and personalized therapeutic strategies.